Eze Goes to School With Moral Lessons - Nzekwu, Onuora and Crowder, Michael (Pilgrim Books Ltd, 1963)
Eze is determined to go to school but this is not easy.Can he overcome the difficulties that stand in his way?...
Keywords: Juvenile Fiction / Adventure